« Décomposition fécondante » : la chimie organique et les savoirs du vivant chez Flaubert - Judith Wulf (Flaubert: Revue Critique et Génétique)
In the 19th century we see the emergence of new ways of conceiving man and living organisms. Flaubert, who does not escape this tendency, involves a wide assortment of natural sciences in his writings, which belongs to a realistic approach, whereas chemistry refers rather to abstract modeling. While the natural sciences are associated with an analytical perspective founded on dissection, chemistry has more to do with composition. And whereas medicine is a familiar discipline for Flaubert, chemistry means incomprehension and widespread doubt. It acts as a counterpoint to the natural sciences to highlight their contradictions. This choice of coupling or separating chemistry and life perfectly mirrors the century’s scientific and philosophical debates. In keeping with his method, Flaubert gives them a voice in his writing.